The Contradiction of Dualism in The Position of Land Banks in Creating a Just Economy - Putra, I Kadek Rey Aditya; Resen, Made Gde Subha Karma (Kertha Patrika; Vol 47 No 1 (2025), 2025)
This study aims to examine the contradiction of the dualism of the position of land banks in creating a just economy based on a comprehensive analysis of the provisions of the Job Creation Law and its derivative rules. This paper uses normative research methods with a literature, conceptual and comparative approach. The results of the study show that Land Banks has two positions, namely as a representative of the state and an implementer of business activities. The dualism of this position is contradictory because on the one hand it must carry out the function of public service and on the other hand consider the orientation of profit. Based on a study of the substance of the regulation of the formation of land banks, its position as the executor of business activities that are full of economic interests has a tendency to dominate more.  The tendency that can be seen from the arrangement of land banks is in the form of siding with the capitalists who own capital without any effort to guarantee the rights of indigenous peoples as marginalized parties. This results in the existence of land banks ignoring efforts to create the greatest possible prosperity for the people as mandated by the constitution which should be a limit on the meaning of the right to control the state. In the end, the equitable economy that was proclaimed as the initial goal of establishing a land bank could not be achieved.